Identification of delirium and subsyndromal delirium in intensive care patients - Alessandra Soler Bastos; Lúcia Marinilza Beccaria; Daniele Cristiny da Silva; Taís Pagliuco Barbosa (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: identify delirium and subsyndromal delirium in intensive care patients; age, hospitalization time, and mortality. Method: a retrospective, quantitative study conducted in the Intensive Care Unit, using the Richmond Agitation-Sedation Scale to evaluate sedation and the Intensive Care Delirium Screening Checklist for the identification of delirium, with the participation of 157 patients. For statistical analysis, the t-test and the Chi-square test was carried out. Results: the majority presented subsyndromal delirium (49.7%). Mortality was 21.7%. The relationship between delirium and its subsyndromal with hospitalization time was statistically significant for both (p=0.035 and p <0.001), while age was significant only in the subsyndromal delirium (p=0.009). Conclusion: the majority of the patients presented subsyndromal delirium. The length of hospital stay was statistically significant in delirium and subsyndroma delirium. Age was significant only in subsyndromal delirium. The mortality of patients with delirium was higher than the others.